Kelengkapan Terapi Medis Sesuai Pedoman dan Dampaknya terhadap Luaran Terapi pada Pasien Angina Pektoris Tidak Stabil: Penelitian di Rumah Sakit Rujukan Tersier di Indonesia - Saufi, Muhammad Rifki; Cholisoh, Zakky (Journal of Pharmaceutical and Sciences, 2026)
Unstable angina pectoris (UAP) is a major cause of cardiovascular hospitalization and requires complex inpatient pharmacological management. Variability in the completeness of core guideline-recommended acute pharmacotherapy may influence inpatient therapeutic outcomes, including length of hospital stay (LOS). This study aimed to evaluate the completeness of core guideline-recommended pharmacotherapy and its association with LOS among hospitalized patients with unstable angina pectoris at a tertiary referral hospital in Indonesia. A descriptive observational study with a retrospective design was conducted using secondary data from medical records. Of 214 hospitalized patients screened, 144 adult patients diagnosed with unstable angina pectoris met the inclusion criteria. Data collected included demographic characteristics, smoking status, comorbidities, LOS, and pharmacological therapy administered during hospitalization. Pharmacotherapy completeness was operationally defined based on the documented use of three core disease-modifying drug classes recommended for the acute management of unstable angina pectoris: antiplatelet therapy (single or dual), statin therapy, and beta-blocker therapy based on core acute-phase recommendations in the ESC 2023 and AHA/ACC 2023 guidelines, at any time during the inpatient stay. Descriptive statistics were used to summarize patient characteristics and medication use, while bivariate analysis was performed to assess the association between pharmacotherapy completeness and LOS. Most patients were male (62.5%) and aged 40–59 years (47.9%) or ≥60 years (43.1%), with a median LOS of 4 days (interquartile range 3–5). The most frequently prescribed drug classes were statins (92.4%), beta-blockers (91.7%), aspirin (88.2%), and angiotensin-converting enzyme inhibitors or angiotensin receptor blockers (86.1%). Dual antiplatelet therapy was administered in 66.7% of patients, and anticoagulants in 28.5%. Bivariate analysis showed no statistically significant association between pharmacotherapy completeness and length of hospital stay (p = 0.642). In conclusion, hospitalized patients with unstable angina pectoris generally received pharmacological therapy aligned with core guideline-recommended acute-phase management. However, the absence of a significant association between pharmacotherapy completeness and LOS suggests that LOS is a multifactorial outcome influenced by clinical and organizational factors beyond pharmacological management. These findings highlight the importance of comprehensive inpatient care and structured medication review, including the role of clinical pharmacists, in optimizing treatment for patients with UAP.